Perilaku Pengurangan Sampah Plastik pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta - Alfira Damayanti; Fini Fajrini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Plastic waste has become a global issue that has a significant impact on the environment and human health. Universities as higher education institutions are also one of the sources of considerable plastic waste due to the daily activities of students and staff. This study aims to identify factors that influence plastic waste reduction behavior among students of the Faculty of Public Health, Universitas Muhammadiyah Jakarta. This research design uses a quantitative approach with a cross-sectional method. A total of 188 students became respondents who were selected by stratified random sampling. Data were collected through an online questionnaire and analyzed using the Chi-Square test with a 95% confidence level. The results showed that the majority of students had good knowledge (77.1%) and positive attitudes (60.1%), but plastic waste reduction behavior was still poor in 52.7% of respondents. A total of 52.1% of students considered government policies related to plastic waste reduction to be good, and statistical analysis showed a significant relationship between government policies and plastic waste reduction behavior (p = 0.026). In contrast, knowledge, attitude, and availability of infrastructure did not have a significant relationship (p > 0.05). The results of this study emphasize that policies have an important role in encouraging changes in behavior that are more concerned about the environment. This study suggests the need to improve supporting facilities, continuous education, and strengthening policy implementation to reduce the use of plastic waste.